Role and importance of financial planning in market conditions - Olena Golovko; Olena Shakhova (Фінансово-кредитна діяльність: проблеми теорії та практики)
The article investigates the theoretical and practical aspects of financial planning businesses and its role in balancing financial resources, relations arising in the process of formation, storage, distribution and use in market conditions.